Prevalence of GIT symptoms in patients of COVID 19 and role of rectal PCR in detecting COVID 19 with GIT symptoms - Ahmed Elmetwally Ahmed; Emad Ahmed Awad; Manal Sabry Mohamed; Abdelrhman Haggag Abdelrady; Moamen Abdelfadil Ismail; Sonya Ahmed Ali El-Gaaly (SpringerOpen, 2024)
Abstract Background In December 2019, a cluster of patients with pneumonia of undetermined etiology was recognized in Wuhan, Hubei, China. Subsequently, a novel coronavirus (Severe Acute Respiratory Distress Syndrome- related Coronavirus) (SARS-CoV-2) was identified from lower respiratory tract samples obtained from affected patients. The clinical manifestation of Coronavirus disease 2019 (COVID 19) is broad and ranges from asymptomatic and mild upper respiratory tract symptoms to severe illnesses with multi-organ failure and death. Furthermore, it is challenging to predict the clinical course or determine patients at risk of deterioration. Aim of the work The aim of our study is to assess prevalence of gastrointestinal tract (GIT) symptoms in COVID 19 infected patients and to assess significance of rectal PCR in detecting COVID 19 patients with gastrointestinal symptoms. Patients and methods This study was conducted on 100 adult COVID 19 patients recently diagnosed by polymerase chain reaction (PCR). All patients were submitted to clinical examination, laboratory testing for Erythrocyte Sedimentation Rate (ESR), C-Reactive Protein,(CRP), Complete Blood Count (CBC), and D-dimer. Radiological investigations in the form of Computed Tomography Chest were reported by radiologist for all patients (High resolution computed tomography). Nasopharyngeal, oropharyngeal and rectal swabs were collected for COVID-19 (PCR) test. All patients received COVID-19 treatment according to protocols of World Health Organization (WHO) and Ministry of Health and Population, Egypt. Results We found that GI symptoms are prevalent among COVID-19 Egyptian patients (64%). The most common GIT symptoms were Nausea, vomiting and diarrhea. We observed that 25 patients (25%) had positive viral RiboNucleic Acid (RNA) in rectal swab. Nausea was manifested in 38 patients (38%), Vomiting was manifested in 24 patients (24%), diarrhea was manifested in 21 patients (21%), pain was manifested in 22 patients (22%), hematemesis was manifested in 3 patients (3%) and melena was manifested in 2 patients (2%). Conclusion The results of current study demonstrated that GIT symptoms are prevalent among COVID-19 Egyptian patients (64%) with Nausea, vomiting and diarrhea to be most common symptoms. Rectal PCR was found in 25 patients, all of them had GIT symptoms but it was statistically non-significant result when compared to the overall number of COVID-19 infected patients. Severe COVID-19 was more frequent in older age.